2008
DOI: 10.1145/1360612.1360625
|View full text |Cite
|
Sign up to set email alerts
|

Clone attack! Perception of crowd variety

Abstract: When simulating large crowds, it is inevitable that the models and motions of many virtual characters will be cloned. However, the perceptual impact of this trade-off has never been studied. In this paper, we consider the ways in which an impression of variety can be created and the perceptual consequences of certain design choices. In a series of experiments designed to test people's perception of variety in crowds, we found that clones of appearance are far easier to detect than motion clones. Furthermore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 23 publications
0
40
0
1
Order By: Relevance
“…McDonnell et al [1], [5] have studied the effects of different types of appearance and motion variation on the perceptibility of visual clones in crowds, while Pražák et al [2] demonstrated how only three different human motions replicated evenly through a crowd. Hoyet et al [6] evaluated the distinctiveness and attractiveness of different types of human motion and found that average motions were the least distinctive and most attractive, consistent with findings in face perception [7].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…McDonnell et al [1], [5] have studied the effects of different types of appearance and motion variation on the perceptibility of visual clones in crowds, while Pražák et al [2] demonstrated how only three different human motions replicated evenly through a crowd. Hoyet et al [6] evaluated the distinctiveness and attractiveness of different types of human motion and found that average motions were the least distinctive and most attractive, consistent with findings in face perception [7].…”
Section: Related Workmentioning
confidence: 99%
“…The perception of varied human appearance and motion have previously been studied in this Note: This work was done while all authors were at Disney Research context [1], [2], but to date, body shape variation has received less attention. However, two of the most functionally relevant and visually salient features of any crowd are the shapes and sizes of the people in it, and their relative distributions: i.e., under normal circumstances most people will have shapes close to the median of the population, and there will be decreasing numbers of more atypical bodies present.…”
Section: Introductionmentioning
confidence: 99%
“…If they all perform the same animation, the results are not realistic enough [11]. In VRlab, we have implemented three techniques to vary the animation of characters, while remaining in the domain of navigating crowds, i.e., working with locomotion animations:…”
Section: How To Vary Animation ?mentioning
confidence: 99%
“…Exactly 20 characters, some of whom were clones, were displayed in four rows of five characters, each placed so that they were optimally visible. In [McDonnell et al 2008], we used reaction times for clicking on pairs of clones as a measure of how effectively clones were disguised. We use this same metric in order to determine the effectiveness of varying only certain body parts.…”
Section: Experiments Proceduresmentioning
confidence: 99%
“…Knowing the parts of the body that are most focused on when viewing crowds would be very useful, as texture memory consumption and computation time could be reduced by varying only those parts of the body that receive the most attention. In [McDonnell et al 2008], we studied the perceptual impact of cloning characters and their motions. We found that appearance variation is most important for creating the illusion of a varied, heterogeneous crowd.…”
Section: Introductionmentioning
confidence: 99%